Comparison of bison and elk susceptibility to experimental challenge with Brucella abortus strain 2308 - S. C. Olsen; P. M. Boggiatto; E. J. Putz (Frontiers in Veterinary Science)
IntroductionBrucellosis is endemic in bison and elk in Yellowstone National Park and surrounding areas.MethodsA comparative study was conducted using data from naive (n = 82 and 67, respectively) and Brucella abortus strain RB51 (RB51) vaccinated (n-99 and 29, respectively) bison and elk experimentally challenged with virulent B. abortus strain during pregnancy.ResultsThe incidence of abortion, fetal infection, uterine or mammary infection, or infection in maternal tissues after experimental challenge was greater (p < 0.05) in naïve and vaccinated bison when compared to similar groups in elk. Vaccinated bison had lower (p < 0.002) abortion rates and recovery of Brucella from fetal or uterine/mammary tissues when compared to naïve bison. Vaccinated elk had reduced (p < 0.01) rates of maternal infection, but rates of abortion and fetal or uterine/mammary infection did not differ (p > 0.05) from naïve elk. Naïve and vaccinated bison had greater (p < 0.05) Brucella colonization in placentomes, and parotid and supramammary lymphatic tissues when compared to elk. In elk or bison that aborted, mean colonization in placentome tissues were typically more than 5 logs higher than in animals that did not abort.DiscussionThe results of our study suggest differences in disease pathogenesis between these two wildlife reservoirs of B. abortus.